Gender differences in practices and interactions in news commentaries in the online newspaper Emol.com - Gheza Correa, Karen (Universidad de Chile. Instituto de la Comunicación e Imagen, 2019)
This research study addresses gender differences in practices and interactions in participatory discussion forums for readers in online press, particularly in news commentaries in the online newspaper found on the website www.Emol.com.